Estimation of infiltration models parameters and their comparison to simulate the onsite soil infiltration characteristics - Farid, Hafiz Umar; Mahmood-Khan, Zahid; Ahmad, Ijaz; Shakoor, Aamir; Anjum, Muhammad Naveed; Iqbal, Muhammad Mazhar; Mubeen, Muhammad; Asghar, Muhammad (International Journal of Agricultural and Biological Engineering, 2019)
Detailed knowledge about soil characteristics and site-specific final steady infiltration rate could help to increase the irrigation water use efficiency and decrease water losses in agricultural system. The experiments were conducted on Agricultural Research Farm of Bahauddin Zakariya University, Multan, Pakistan during 2016. The cumulative infiltration depth was measured using double ring infiltrometer at selected six points of the study area. Most commonly used infiltration models such as Kostikov’s, Philip’s and Horton’s were fitted to the field infiltration data for determination of model parameters and to find the best fit model for the study area. Kostikov’s infiltration model’s parameters such as empirical constant ‘c’ and infiltration decay constants ‘k’ were obtained in the ranges of 0.140-0.290 and 0.307-0.433, respectively. Philip’s infiltration model’s parameters such as sorptivity ‘S’ and conductivity constant ‘A’ were found in the ranges of 0.167-0.288 cm/min1/2 and –0.001 to –0.009 cm/min, respectively. Similarly, the Horton’s model’s ‘parameter ‘k’ was obtained in the range of –1.619 to –1.238. The value of infiltration capacity at onset of infiltration (fo) was obtained as 1.744 to 3.491 for all the six points. The analysis showed that the infiltration models using the estimated parameters have satisfactory prediction capability at all the selected points. Horton’s model provided the lowest mean values for RMSE (0.235) and highest mean values for ME (94%); and the lowest mean values for MPD (0.127). This indicated that infiltration can be well-described by the Horton’s model at the selected site. Keywords: infiltration characteristics, infiltration models, parameters estimation, perdition capability DOI: 10.25165/j.ijabe.20191203.4015 Citation: Farid H U, Mahmood-Khan Z, Ahmad I, Shakoor A, Anjum M N, Iqbal M M, et al. Estimation of infiltration models parameters and their comparison to simulate the onsite soil infiltration characteristics. Int J Agric & Biol Eng, 2019; 12(3): 84–91.